Drivers of Air‐Sea CO2 Flux Seasonality and its Long‐Term Changes in the NASA‐GISS Model CMIP6 Submission. (16th February 2021) - Lerner, Paul; Romanou, Anastasia; Kelley, Maxwell; Romanski, Joy; Ruedy, Reto; Russell, Gary
Abstract: Climate change will affect both the mean state and seasonality of marine physical and biogeochemical properties, with important implications for the oceanic sink of atmospheric CO2 . Here, we investigate the seasonal cycle of the air‐sea exchange of CO2 and pCO2, sw (surface seawater pCO2 ) and their long term changes using the CMIP6 submission of the NASA‐GISS modelE (GISS‐E2.1‐G). In comparison to the CMIP5 submission (GISS‐E2‐R), we find that on the global scale, the seasonal cycles of the CO2 flux and NPP have improved, while the seasonal cycles of dissolved inorganic carbon (DIC), alkalinity, and macronutrients have deteriorated. Moreover, for all ocean biogeochemistry fields, changes in skill between E2.1‐G and E2‐R display large regional variability. For E2.1‐G, we find similar modeled and observed CO2 flux seasonal cycles in the subtropical gyres, where seasonal anomalies of pCO2, sw and the flux are temperature‐driven, and the Southern Ocean, where anomalies are DIC‐driven. Biases in these seasonal cycles are largest in the subpolar and equatorial regions, driven by a combination of biases in temperature, DIC, alkalinity, and wind speed. When comparing the historical simulation to a simulation with an idealized increase in atmospheric pCO2, we find that the seasonal amplitudes of the CO2 flux and pCO2, sw generally increase. These changes are produced by increases in the sensitivity of pCO2, sw to its respective drivers. These findings are consistent with the notion that the seasonality of pCO2, sw is expected to increase due to the increase of atmospheric pCO2, with changes in the seasonality of temperature, DIC, and alkalinity having secondary influences. Plain Language Summary: The ocean plays an important role in removing human CO2 emissions from the atmosphere. The removal varies seasonally, and this variability is expected to change as the ocean's carbon content increases. To predict these changes, models need to accurately simulate seasonal changes of the air‐sea exchange of CO2 . In this study, we examine the seasonal cycle of the air‐sea exchange of CO2 in the CMIP6 version of the NASA‐GISS modelE (GISS‐E2.1‐G). We find good agreement between the seasonal cycles in the model and observations in the subtropical latitudes, where seasonal changes are mainly caused by temperature changes, and in the Southern Ocean, where seasonal changes are mainly caused by changes in dissolved inorganic carbon (DIC). Agreement is much poorer in high latitudes and tropical waters, where discrepancies in model wind speed, temperature, DIC, and alkalinity all contribute to differences between the modeled and observed seasonal cycle of air‐sea CO2 exchange. We further find, under future atmospheric CO2 increase, that seasonal extremes in the air‐sea exchange of CO2 increase in most of the ocean. Our findings support the idea that, under increased CO2 levels, the change in the ocean's ability to take CO2 from the atmosphere will be seasonally dependent. Key Points: The seasonality of the CO2 flux, pCO2, and their drivers in the NASA‐GISS model are evaluated using a suite of monthly climatologies The seasonal cycles of the CO2 flux and pCO2, sw are temperature‐driven in the subtropics and DIC‐driven in the Southern Ocean In an idealized future forcing scenario, changes in the flux are largely driven by changes in the sensitivity of pCO2 to its drivers